Improving the biocontrol potential of Steinernema feltiae against Delia radicum through dosage, application technique and timing. Issue 5 (7th October 2013) - Beck, Bert; Spanoghe, Pieter; Moens, Maurice; Brusselman, Eva; Temmerman, Femke; Pollet, Sabien; Nuyttens, David
Abstract BACKGROUND The potential of the entomopathogenic nematode (EPN) Steinernema feltiae Filipjev as a biocontrol agent against the cabbage maggot Delia radicum (L.), was assessed in three field tests, focusing on EPN dosage, application technique and timing. RESULTS Spraying cabbage plant trays with different doses of infective juveniles (IJs) (50 000, 100 000 and 200 000 per plant) generated a similar reduction of plant mortality. Spraying plant trays with 200 000 IJs of Steinernema feltiae per plant temporarily reduced the number of maggots around the plants' roots, while neither spraying a lower dose (50 000 IJs/plant) nor soil drenching with 200 000 or 50 000 IJs/plant) reduced maggot numbers. When applied as a plant tray spray, IJs of S. feltiae took 1–2 weeks to spread through the soil surrounding the roots. The pathogenicity of the EPNs, as evaluated by a Galleria mellonella bait test, was highest (up to 100% mortality) until up to five weeks after application, and declined to control levels after 4–7 weeks. Follow‐up drench applications with EPNs, applied one and/or two weeks after the first EPN application, did not influence control of Delia radicum. CONCLUSION Plant tray spraying provides better placement of Steinernema feltiae than soil drench treatments for control of Delia radicum. Plant mortality was not dose‐dependent in the presented trials, unlike the reduction of maggot numbers. Further research into timing and application technique of follow‐up treatments with S. feltiae is required to increase efficacy to commercial standards. © 2013 Society of Chemical Industry